Direct Printing of Thermal Management Device Using Low‐Cost Composite Ink. Issue 10 (30th June 2017) - Nguyen, Nam; Melamed, Eric; Park, Jin Gyu; Zhang, Songlin; Hao, Ayou; Liang, Richard
Abstract : Light weight and low‐cost thermal devices such as heat sink are fabricated using direct ink printing of epoxy with hybrid filler including carbon fiber and graphite nanoplatelets. Printed structure shows good thermal conductivity of 2 W m −1 K −1 . This work can open new methods to fabricate low cost and high performance thermal devices. Abstract : This work presents a new method for fabricating thermal devices, such as heat sinks, using a 3D printing technique and lightweight composite ink. The method focuses on formulating composite inks with desired properties and direct ink writing for manufacturing. The ink undergoes two phases: phase one uses low viscosity epoxy to provide viscoelastic properties and phase two provides the fillers consisting of carbon fiber and graphite nanoplatelets to provide high thermal conductivity and structural properties. By combining these functional materials, 3D structures with a high thermal conductivity (≈2 W m −1 K −1 ) are printed for thermal management applications with the storage modulus of 3000 MPa and a density only 1.24 g cm −3 . The results show that by carefully tailoring functional properties of the ink, net‐shape multifunctional structures can be directly printed for thermal management device applications, such as heat sinks.